Gestão de resíduos sólidos: ações educativas no Colégio Estadual de Tempo Integral Edgar Silva em Andaraí na Chapada Diamantina (Ba) - Santos, Steve Wander Teixeira dos (2024)
Contemporary society has been facing countless challenges over the centuries, directly linked to its way of life, highlighting among them those related to the inadequate disposal of Solid Waste which, generated by various human activities, are the source of several environmental problems, economic, social and health. In view of the above, managing this waste appropriately becomes imperative, and it is in this context that the Colégio Estadual de Tempo Integral Edgar Silva is inserted, the school where the research was carried out, which faces the problems arising from the disposal of these materials, without , however, have a proposal to improve its management. Based on this study, educational actions were developed on the issue of Solid Waste at the College, which were developed in four stages: i) moments of awareness and formation of a research group; ii) carrying out training cycles with the application of a semi-structured form to survey prior knowledge, carry out diagnoses, training meetings to address topics related to the subject, and gravimetric analysis of waste produced at the school; iii) preparation of an action plan with a solid waste management strategy; iv) dissemination of results to the school community; and, v) evaluation. To reach the objectives, participatory research was used, which has as its principle action research, which enables the involvement of users of the school system in search of resolving their problems. This work had a great impact on the school community, as in addition to promoting the improvement of Solid Waste management, it promoted several educational actions, which demonstrated that the school is an important space for disseminating information on the topic. The study, which included the participation and engagement of the entire school community, showed that it is possible and necessary to approach the 2030 Agenda and its Sustainable Development Goals based on the development of educational actions. It was also revealed that it is possible to work on interdisciplinarity with the subjects that make up the curricular matrix, in dialogue with the topic of solid waste, further demonstrating that participatory methodologies are effective tools in implementing such processes. Finally, it is worth highlighting that some challenges were faced during this journey, however, once the obstacles were overcome, the actors and actresses who work in the school community were able to develop an action plan with strategies for managing this waste, which contains suggestions for improving school solid waste management.